Fundamental study on the effect of alkaline treatment on natural fibers structures and behaviors - Muhammad Khusairy, Bakri; Elammaran, Jayamani; Sinin, Hamdan; Md Rezaur, Rahman; Kokheng, Soon; Akshay, Kakar (Asian Research Publishing Network, 2016)
In composites, chemical treatment caused better adhesion interface between fibers and polymer. Thus, in this research, alkaline treatment was performed on jute and kenaf fibers in an alkaline solution containing 5wt % sodium hydroxide diluted with distilled water, at room temperature for 30 minutes. The pH levels of the alkaline solution were maintained approximately at pH 11 to pH 12. The untreated and treated fibers were analyzed using Fourier transform infrared (FTIR) spectroscopy in the range of 4000 cm-1 to 400 cm-1. It is found out that change in the structure and the removal of outer cell layers, cellulose, hemicellulose, lignin, waxes and other impurities during the alkaline treatment that affected the improvement on the adhesion interface between fibers and polymer.